Intolerance of uncertainty and adjustment among paramedical students: a cross-sectional study - Putusenla,; Swati,; Saran, Brijesh; Debapriya, (International Journal of Research in Medical Sciences, 2025)
Background: Working in the healthcare settings can be complex and ever-changing requiring adaptability and ability to manage stress in unclear circumstances. Paramedical students enter a field with a demanding nature of training and future professional responsibilities, needing high tolerance for uncertainty. As well as students may struggle to balance their studies with personal responsibilities and social life which can impact their ability to adjust. Therefore, the study is aimed to assess the relationship between intolerance of uncertainty (IU) and adjustment among paramedical students. Methods: A cross-sectional study was conducted among 287 paramedical students from Santosh Deemed to be University in Ghaziabad, Uttar Pradesh, India. Data were collected using validated tools to measure their IU and adjustment. Analysis was done using SPSS and MS excel. Results: The findings revealed that a considerable proportion (64.1%) of paramedical students exhibited high levels of IU. Analysis of adjustment levels showed that among males, the majority (62%) had overall unsatisfactory adjustment, while similar patterns were observed among females (50.3%). Chi-square analysis demonstrated a statistically significant relationship between IU scale (IUS) and adjustment levels in both genders. Chi-Square values for females (χ²=132.957) and males (χ²=110.467) were highly significant (p<0.01). Conclusions: The findings highlight that a significant number of paramedical students experience high IU, which is strongly associated with poor adjustment to college life. These results emphasize the need to incorporate psychological support, uncertainty tolerance training, and adjustment strategies into paramedical education. Enhancing these areas may improve students’ well-being, academic performance, and future professional competence.